La fidelidad de los usuarios en la cooperativa de transportes Sangay, y su incidencia en la calidad del servicio en la Provincia de Chimborazo, Ciudad de Riobamba, Período 2016. - Parra López, Jhoselin Tatiana (2018)
In the present work of titulación a study on "The Fidelity of the users in the Cooperative of Transports Sangay, and its Incidence in the Quality of the Service in the Province of Chimborazo, City of Riobamba, Period 2016.", that allowed to the institution knows precisely its position in the transport sector in order to provide solutions that improve and strengthen the internal performance of the institution. In the introduction the problem was detailed, the problematization and the hypothesis that was verified through the fulfillment of the objectives. The State of Art; It was composed in its first part by the background of the research, and in its second part detailed its theoretical foundation through the conceptualization of each of the variables of research. In the methodology, it was pointed out how this research was developed, in addition to defining the population and sample in which the study was conducted; and, in the Results and Discussion; An analysis was established that allowed to determine the conclusions and recommendations of the present titration work.